Respostas
respondido por:
0
Resposta:
A)28 B)20
Explicação passo-a-passo:
A) (-3)^2 -3*(-3) +10 = 9 + 9 + 10 = 28
B) (5)^2 -3*5 +10 = 25 - 15 + 10 = 20
respondido por:
1
Resposta:
x² - 3x - 10 = 0
delta = (-3)² - 4.1.(-10)
delta = 9 + 40
delta = 49
x = (-(-3)+/-\/49)/2.1
x = (3+/-7)/2
x' = (3+7)/2 --> x' = 10/2 --> x' = 5
x" = (3-7)/2 --> x" = -4/2 --> x" = -2
as raízes são -2 e 5
Explicação passo-a-passo:
Espero ter ajudado
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás